Assessment of occupational noise expose among construction workers in a selected construction site in Putrajaya, Malaysia / Mohd Ezwan Wahid - Mohd Ezwan , Wahid (2018)
In 2017, in Putrajaya alone have more than 30 on-going construction sites. More than 6000 man power either local or foreigner involved. To maintain as a well and fast-pace developed country, extra attention need to be given to this industry. When one talks about hazard of building construction, one always mentions about physical hazard such as work at height. Seldom we discuss on health hazards of it. One of the health hazards that present in this industry is noise. Therefore, this study is focusing on the objective which is to measure the noise level of all type of work (construction & structure, architectural and mechanical & electrical) in building construction activity, determine factor that contribute to source of noise and its control and PPE to overcome them and lastly to determine level of awareness among construction personnel towards noise hazard. To meet the objectives for this research, area noise monitoring, personal noise monitoring and survey form have been used. Result of the noise monitoring show that some activities exceed the action level of noise while result of survey show that awareness of construction personnel toward noise hazard as overall is still considered below average.